Field reports of Iowa birds, June 22, 1985 - Kent, Thomas H. (Thomas Hugh), 1934-et al (1985)
List of bird sightings from across the state compiled by Thomas H. Kent. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly Report of spring 1985. Epson - sheet feed